1988
DOI: 10.1021/j100315a019
|View full text |Cite
|
Sign up to set email alerts
|

Surface-enhanced Raman spectra of pyrazine, pyrimidine, and pyridazine adsorbed on silver sols

Abstract: Raman) for its verification. The low excited-state torsional barriers suggest some possibilities for the photochemical dynamics of this elementary conjugated hydrocarbon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 0 publications
9
54
0
Order By: Relevance
“…10 agree well with those from roughened silver electrodes, 17,19 which concluded that the pyrazine was adsorbed onto the substrate in an end-on configuration with probably a slightly tilted configuration. 20 -22 Our SERS spectrum of pyrazine at OCP is also quite similar to the SERS spectrum of pyrazine on the aggregated silver sol reported by Muniz-Miranda et al 40,41 The spectra show several similarities to the aqueous pyrazine spectrum, including the fact that the 1023 cm 1 band is the strongest and is about eight times stronger than the 1595 cm 1 band.…”
Section: Comparison Between the Observed And Calculated Infrared Ramsupporting
confidence: 81%
“…10 agree well with those from roughened silver electrodes, 17,19 which concluded that the pyrazine was adsorbed onto the substrate in an end-on configuration with probably a slightly tilted configuration. 20 -22 Our SERS spectrum of pyrazine at OCP is also quite similar to the SERS spectrum of pyrazine on the aggregated silver sol reported by Muniz-Miranda et al 40,41 The spectra show several similarities to the aqueous pyrazine spectrum, including the fact that the 1023 cm 1 band is the strongest and is about eight times stronger than the 1595 cm 1 band.…”
Section: Comparison Between the Observed And Calculated Infrared Ramsupporting
confidence: 81%
“…The origin of SERS still remains a matter of controversy, though it is now widely accepted that there are two main contributions to the overall effect. One is the classical electromagnetic contribution through the surface plasmon resonance by the exciting electromagnetic field [1] and the other is the chemisorption which involves chargetransfer interaction between the adsorbed molecule and the metal surface [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of this enhancement is broadly explained in terms of electromagnetic 1 -3 and chemical interactions. 4,5 With the vibrational information available from this technique, the molecular forms and the orientation of the adsorbed species on the metal surfaces can be investigated. 1,6 -9 Since the discovery of SERS, pyridine and its substituted derivatives have been extensively studied, 10 -13 which made a major contribution to the understanding of the SERS mechanism involved in these cases and also in estimating their possible orientations on a roughened silver surface.…”
Section: Introductionmentioning
confidence: 99%